Teachers understanding teaching a multimedia hypertext tool - Johnson, Karen E.; Johnson, Glenn (Boston, MA : Heinle & Heinle, 1998)
Designed for professional development programs, teacher in-service programs, or independent use, this video can be used by second and foreign language instructors who want to improve their teaching skills
Series editor, Donald Freeman
Keywords: Teachers -- In-service training -- United States; Teacher effectiveness -- United States